A calmodulin-like protein suppresses RNA silencing and promotes geminivirus infection by degrading SGS3 via the autophagy pathway in Nicotiana benthamiana. - Fangfang Li; Nan Zhao; Zhenghe Li; Xiongbiao Xu; Yaqin Wang; Xiuling Yang; Shu-Sheng Liu; Aiming Wang; Xueping Zhou (PLoS Pathogens)
A recently characterized calmodulin-like protein is an endogenous RNA silencing suppressor that suppresses sense-RNA induced post-transcriptional gene silencing (S-PTGS) and enhances virus infection, but the mechanism underlying calmodulin-like protein-mediated S-PTGS suppression is obscure. Here, we show that a calmodulin-like protein from Nicotiana benthamiana (NbCaM) interacts with Suppressor of Gene Silencing 3 (NbSGS3). Deletion analyses showed that domains essential for the interaction between NbSGS3 and NbCaM are also required for the subcellular localization of NbSGS3 and NbCaM suppressor activity. Overexpression of NbCaM reduced the number of NbSGS3-associated granules by degrading NbSGS3 protein accumulation in the cytoplasm. This NbCaM-mediated NbSGS3 degradation was sensitive to the autophagy inhibitors 3-methyladenine and E64d, and was compromised when key autophagy genes of the phosphatidylinositol 3-kinase (PI3K) complex were knocked down. Meanwhile, silencing of key autophagy genes within the PI3K complex inhibited geminivirus infection. Taken together these data suggest that NbCaM acts as a suppressor of RNA silencing by degrading NbSGS3 through the autophagy pathway.